Kewenangan Pengadilan Negeri Memutus Perkara Praperadilan Mengenai Tidak Sahnya Penetapan Tersangka - Ida Ayu Wayan Widyastuti; Anak Agung Sagung Laksmi Dewi; I Nyoman Gede Sugiartha (Jurnal Analogi Hukum, 2020)
Abstract—Pre-trial institutions have the purpose of providing certainty and controlling abuse of authority by law enforcement officials. Forced measures such as arrest, detention, search, confiscation, prosecution and determination of suspects carried out in accordance with the provisions of legislation are often used by law enforcement officials to obtain evidence. The problem raised is how is the regulation of the authority of the district court to decide the pretrial lawsuit? How is the procedure for hearing a pretrial hearing? This research is a study that examines legislation as an effort to answer existing problems. The authority of the district court checks and decides on a pretrial case in accordance with what is stipulated in article 77 of the Criminal Procedure Code. While the procedure for examining pretrial hearings is the procedure that must be fulfilled, namely Submission of pretrial applications, Application for registration in pretrial cases, Head of District Court Immediately Appoints Judges and Registrars, Examinations are conducted with a single judge. Law enforcement agencies, in this case the police as one of the justice enforcement agencies must be carried out by its members responsibly and carried out wholeheartedly and in accordance with the laws and regulations. The community as being protected must have a critical nature and at least know the inspection procedures in the police so that they understand their rights when dealing with the law .